The Academic Mobility of Students for Whom English is Not a First Language: The Roles of Ethnicity, Language, and Class - Garnett, Bruce; Adamuti-Trache, Maria; Ungerleider, Charles (Alberta Journal of Educational Research, 2008)
This study uses extant data to examine the roles of ethnicity, social class, and linguistic proficiency in predicting the participation and performance of students for whom English is not a first language (ENFL) from the class of 2002 in a provincially examinable grade 12 subject areas in a large urban British Columbia school district (n=4,075). Descriptive statistics show similar performance levels, but variable participation rates among ENFL and native English-speaking (NES) baseline students. However, these results mask differences between ethnolinguistic subgroups of ENFL students. Linear and logistic regressions show that although social class and linguistic proficiency significantly affect outcomes, participation and performance advantages to Chinese- and Korean-speaking students over their ENFL and NES peers hold across the sciences. Smaller performance advantages to Chinese speakers hold across the humanities.